Pengaruh Senam Lansia Terhadap Kualitas Tidur Lansia: Pengabdian - Betty Sunaryanti; Sunaryo Joko Waluyo (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Sleep is a condition where a person is not aware because the individual's perception of the environment is decreased or lost, in this condition a person can be awakened again with sufficient stimulation. Rest and sleep are basic needs that must be met by everyone. Normal sleep involves two phases, namely rapid eye movement (REM) and sleep with non-rapid eye movement (NREM). Changes in sleep patterns in the elderly are caused by changes in the neurological system which physiologically will decrease the number and size of neurons in the central nervous system which causes sleep disorders. To analyze the relationship between elderly exercise and sleep quality in the elderly based on the Pittsburgh Sleep Quality Indexs (PSQI) score. Analysis of the data used Spearman rank correlation (non-parametric) does not require normally distributed data. This test aims to determine the relationship between variables. The interpretation of this analysis is intended to see the significance of the relationship, the strength of the relationship and the direction of the relationship. The basis for decision making is if the significance value is <0.05 then it is correlated (there is a relationship), otherwise if the significance value is> 0.05 then it is not correlated (There is no relationship). The study sample was 10 elderly people who met the inclusion and exclusion criteria. The measurement of sleep quality used the PSQI questionnaire. There is a P value of 0.03, which means P. Value <0.05, so it can be concluded that there is a significant relationship between elderly exercise and the quality of sleep in the elderly with a strength of 1,000 so that it has a perfect relationship between elderly exercise and elderly sleep quality.